A carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance and a preparation method thereof

CN117089026BActive Publication Date: 2026-10-16JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311077268.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2026-10-16
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

此类无机纳米粒子在与聚合物杂化的过程中会由于表面能较高而出现聚集的现象,进而导致导光板导光性能下降,透光性较差;同时部分种类的无机纳米粒子能带较窄,具有一定的光催化性质,会引起聚合物的老化,进而降低导光板的使用性能

Benefits of technology

[0005] The purpose of this invention is to provide a carbonized polymer dot/polymer hybrid light guide plate with high visible light transmittance and its preparation method. The preparation process is simple, the materials are non-toxic and harmless, which is in line with the concept of green development. The light guide plate prepared has high visible light transmittance in the vertical direction, high light output brightness on the surface, and high uniformity, thus overcoming the defects of the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117089026B_ABST
    Figure CN117089026B_ABST
Patent Text Reader

Abstract

The application discloses a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance and a preparation method thereof, and belongs to the technical field of light guide plates. First, 0.1-5 parts of mHRI-CPDs with polymerizable groups on the surface are dissolved in 100 parts of polymerizable active monomers, and then the mixture is stirred at room temperature for 3-8 minutes and is subjected to ultrasonic oscillation in a 60-100 W ultrasonic oscillator for 3-8 minutes. Then, 0.1-0.5 parts of initiator 1 or initiator 2 is added into the obtained mixed solution, and the mixture is stirred at room temperature for 3-8 minutes to configure a precursor solution. The precursor solution is prepared into the light guide plate through thermal curing or photocuring, and the light brightness and uniformity can be adjusted by adjusting the concentration of the mHRI-CPDs. The preparation method is simple, the material is non-toxic and harmless, and the method conforms to the green development concept. The prepared light guide plate has high visible light transmittance in the vertical direction, high light brightness on the surface and high uniformity, and the defects of the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of light guide plate technology, specifically relating to a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance and its preparation method. This light guide plate can be used in technologies such as double-sided LCD displays, transparent LCD displays, and full-screen LCD displays. Background Technology

[0002] Light guide plates are a new type of light-guiding material made from polymethyl methacrylate (PMMA), polycarbonate (PC), or polystyrene (PS) as substrates, using ultraviolet printing, chemical etching, laser engraving, and nanotechnology. The function of a light guide plate is to guide light entering the plate through reflection and refraction via its bottom structure or dots, allowing the light to diffuse evenly and effectively, thus converting point or line light sources into surface light sources, which then exit from the light-emitting surface of the plate. Common manufacturing processes for light guide plates include ultraviolet printing, chemical etching, injection molding, and laser engraving. However, these methods suffer from drawbacks such as the inability to easily cut the finished product, complex equipment, low yield, high energy consumption, and difficulty in mass production. Furthermore, these methods involve destructive processing, resulting in light guide plates with only one light-emitting surface, making double-sided light guiding difficult. However, current technologies such as transparent LCD displays and full-screen LCDs (with hidden cameras under the screen) require light guide plates with excellent light-guiding performance and high visible light transmittance.

[0003] To achieve the above objectives, novel light guide plates doped with nanoparticles have been proposed in recent years, also known as nano-light guide plates. Compared to light guide plates produced using traditional manufacturing processes, the working principle of these plates differs in that nanoparticles replace light guide dots. These nanoparticles are distributed throughout the entire light guide plate. When light arrives, the nanoparticles scatter the light, transforming point or line light sources into surface light sources, which then exit from the light guide plate's emission surface. Common nanoparticles include inorganic nanoparticles such as nano-silica, nano-titanium dioxide, nano-zirconium dioxide, and nano-alumina. During hybridization with polymers, these inorganic nanoparticles tend to aggregate due to their high surface energy, leading to a decrease in the light guide plate's light-guiding performance and poor light transmittance. Furthermore, some types of inorganic nanoparticles have narrow band structures and exhibit photocatalytic properties, which can cause polymer aging, further reducing the performance of the light guide plate.

[0004] Therefore, there is an urgent need for a new type of nanoparticle with a high refractive index, which can induce light scattering behavior in a polymer matrix, resulting in high surface light intensity and uniformity in the light guide plate. Simultaneously, it should exhibit good compatibility with polymer materials, thereby improving the visible light transmittance of the light guide plate. Carbonized polymer dots, as nanoparticles with a core-shell structure and a size less than 20 nm, possess a dense internal core and a surface "shell" of reactive functional groups or polymer chains. The internal "core" provides the carbonized polymer dots with a high refractive index, while the surface "shell" enhances their compatibility with the polymer matrix. Furthermore, carbonized polymer dots are non-toxic, harmless, and easy to produce, making them a high-performance organic-inorganic hybrid nanoparticle that holds promise for solving the aforementioned problems. Summary of the Invention

[0005] The purpose of this invention is to provide a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance and its preparation method. The preparation process is simple, the materials are non-toxic and harmless, which is in line with the concept of green development. The light guide plate prepared has high visible light transmittance in the vertical direction, high light output brightness on the surface, and high uniformity, thus overcoming the defects of the prior art.

[0006] A method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance, comprising the following steps:

[0007] a. Dissolve 0.1 to 5 parts by mass of mHRI-CPDs with polymerizable groups on the surface in 100 parts by mass of polymerizable active monomer to obtain mixed solution A;

[0008] b. Stir the mixed solution A prepared in step a at room temperature for 3-8 minutes, and then sonicate it in a 60-100W ultrasonic oscillator for 3-8 minutes; then add 0.1-0.5 parts by weight of initiator 1 to the mixed solution, stir at room temperature for 3-8 minutes to prepare a precursor solution; inject the precursor solution into a cuboid mold, evacuate for 1-3 minutes to remove air bubbles, first thermally polymerize at 50-70℃ for 10-15 hours, then thermally polymerize at 75-85℃ for 1-3 hours, and finally anneal at 100-110℃ for 1-2 hours to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance (thermosetting to prepare the light guide plate);

[0009] Alternatively, stir the mixed solution A prepared in step a at room temperature for 3–8 minutes, and then sonicate it in a 60–100W ultrasonic oscillator for 3–8 minutes. Then, add 0.1–0.5 parts by weight of initiator 2 to the mixed solution, stir at room temperature for 3–8 minutes, and prepare a precursor solution. Inject the precursor solution into a cuboid mold, evacuate for 1–3 minutes to remove air bubbles, first place it in front of a 40–60W UV curing lamp for 1–3 hours, then thermally polymerize it at 75–85℃ for 1–3 hours, and finally anneal it at 100–110℃ for 1–2 hours to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance (photocuring preparation of light guide plate).

[0010] Preferably, the polymerizable active monomer in step a is one or a mixture of several of allyl diethylene glycol carbonate, styrene, methyl acrylate, methyl methacrylate, butyl methacrylate, and N,N-dimethylacrylamide.

[0011] Preferably, the initiator 1 mentioned in step b is one or a mixture of several of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, dicumyl peroxide, and tert-butyl peroxide.

[0012] Preferably, the initiator 2 mentioned in step b is one or a mixture of several of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone (PI 1173), 1-hydroxy-cyclohexyl-phenyl ketone (PI 184), and benzophenone, or one or a mixture of several of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, and benzophenone with one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, dicumyl peroxide, and tert-butyl peroxide. A mixture of several substances; one or more of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, and benzophenone are used in a mass ratio of 3 to 5:1 with one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, dicumyl peroxide, and tert-butyl peroxide.

[0013] Preferably, the thickness of the prepared high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate is 0.1 to 20 mm.

[0014] Preferably, the light output brightness and uniformity of the high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate can be adjusted by adjusting the mHRI-CPDs concentration.

[0015] Preferably, the preparation method of the mHRI-CPDs with polymerizable groups modified on the surface in step a is as follows:

[0016] (1) Preparation of HRI-CPDs by hydrothermal method

[0017] Weigh 2-aminobenzylthiophenol and thiosalicylic acid in a molar ratio of 1:0.8-1.2 and dissolve them in an acidic aqueous solution. After ultrasonic vibration to ensure homogeneity, transfer the mixture to a hydrothermal reactor and react at 140-220℃ for 2-8 hours. After the reaction, remove the supernatant by centrifugation. Wash the bottom precipitate 3-5 times with dichloromethane and then dry it at 20-40℃ to obtain HRI-CPDs.

[0018] (2) Preparation of mHRI-CPDs

[0019] The HRI-CPDs prepared in step (1) and an equal mass of acid-binding agent were added to anhydrous organic solvent, and the mixture was placed in an ice-salt bath to lower the temperature to -10 to 0°C. The mixture was stirred for 10 to 20 minutes to obtain a mixed solution. A surface modifier of equal mass to HRI-CPDs was added to the mixed solution while stirring, and the reaction was carried out for 1 to 10 hours. After the reaction was completed, the reaction mixture was filtered, and the organic solvent was removed from the filtrate by vacuum distillation to obtain mHRI-CPDs.

[0020] Preferably, the particle size of HRI-CPDs and mHRI-CPDs is between 2 and 10 nanometers.

[0021] Preferably, in step (1), thiosalicylic acid can be replaced by one or more of 2,2'-dithiodibenzoic acid (A) and salicylic acid (B), and 2-aminothiophenol can be replaced by one or more of p-aminothiophenol (C), m-aminothiophenol (D), m-aminophenol (E), p-aminophenol (F), and o-aminophenol (G), as shown in the following structural formula:

[0022]

[0023] Preferably, in step (1), the acidic aqueous solution contains one or more of formic acid, acetic acid, and propionic acid, and the total volume of acid and water is 100%, of which the volume of acid is 20% to 90%.

[0024] Preferably, in step (2), the acid-binding agent is one or more of N-diisopropylethylamine, triethylamine, pyridine, sodium acetate, sodium carbonate, and potassium carbonate.

[0025] Preferably, in step (2), the anhydrous organic solvent is one or more of anhydrous acetone, anhydrous acetonitrile, anhydrous tetrahydrofuran, anhydrous 1,4-dioxane, and anhydrous propylene glycol methyl ether acetate.

[0026] Preferably, in step (2), the surface modifier used is one or more of acryloyl chloride (H), methacryloyl chloride (I), 2-butenoyl chloride (J), 3,3-dimethylacryloyl chloride (K), cinnamoyl chloride (L), and p-fluorocinnamoyl chloride (M), with the following structural formula:

[0027] Attached Figure Description

[0028] Figure 1 The 1H NMR spectrum of the mHRI-CPDs prepared in Example 1 shows that the acryloyloxy group has been successfully modified on the surface of the carbonized polymer dots.

[0029] Figure 2 : A schematic diagram of the high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate structure of the present invention, wherein the carbonized polymer dots act as light scattering units;

[0030] Figure 3 Transmission electron microscopy images of HRI-CPDs prepared in Example 2 show that the HRI-CPDs have a uniform particle size distribution.

[0031] Figure 4 Transmission electron microscopy (TEM) image of an ultrathin section of a light guide plate prepared with a doping concentration of 1.0 wt% in Example 2, showing the dispersion of carbonized polymer dots in the polymer.

[0032] Figure 5 (a): A schematic diagram of the high visible light transmittance of the carbonized polymer dot / polymer hybrid light guide plate prepared in Example 3. The visible light transmittance is very high and there is almost no color.

[0033] Figure 5 (b): A view of the carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance prepared in Example 3 before light guiding and illumination;

[0034] Figure 5 (c): A schematic diagram of the light guiding effect of the high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate prepared in Example 3.

[0035] Figure 6 Example 4: The high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate is used in an LCD display screen. (a) The image shows the display effect of the LCD screen before the backlight of the light guide plate is turned on. (b) The image shows the display effect of the LCD screen after the backlight of the light guide plate is turned on. It can be seen that the screen brightness is uniform and the brightness is high.

[0036] Figure 7The ultraviolet-visible transmission spectra of the light guide plates prepared in each embodiment show that each embodiment exhibits a visible light transmittance of greater than 85%, with the visible light transmittance of each group of light guide plates in Example 1 being greater than 90%.

[0037] Table 1: Performance parameters of the light guide plates prepared in each embodiment

[0038]

[0039] Note: The severity of the effect is displayed from best to worst as Excellent+, Excellent, Good, and Poor. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0041] Example 1

[0042] 875 μL of 2-aminobenzylthiophenol and 2031 mg of 2,2'-dithiobenzoic acid were dissolved in 40 mL of a mixture of formic acid and deionized water (volume ratio of formic acid to deionized water 4:6). The mixture was ultrasonically vibrated to ensure homogeneity and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 160 °C for 8 hours. After the reaction, the solution in the reactor was centrifuged at 10,000 rpm for 5 minutes to remove the supernatant. The bottom precipitate was washed three times with dichloromethane. The resulting powder was dried in an oven at 40 °C to obtain 1132 mg of HRI-CPDs. The average particle size of the HRI-CPDs was 5.2 nm, and the refractive index at 473 nm was 1.7332.

[0043] The obtained 1132 mg of HRI-CPDs and an equal mass of pyridine were added to anhydrous acetone, and the mixture was placed in an ice-water bath to lower the temperature to 0°C. After stirring for 10 minutes, a mixed solution was obtained. 1132 mg of acryloyl chloride was added dropwise to this mixed solution while stirring. After stirring for 1 hour, the reaction was stopped. The reaction mixture was filtered to remove insoluble solids. The filtrate was then subjected to vacuum distillation to remove the organic solvent, yielding 1021 mg of mHRI-CPDs with surface-modified acryloyloxy polymerizable groups. Figure 1 The 1H NMR spectrum of the mHRI-CPDs shows obvious characteristic hydrogen peaks of acryloyloxy groups on the surface. The peak area and splitting pattern are consistent with the theory, which indicates that the acryloyloxy groups have been successfully modified on the surface of the carbonized polymer dots.

[0044] 400 mg of mHRI-CPDs with surface-modified acryloyloxy polymerizable groups were dissolved in 40 g of methyl methacrylate. The resulting mixture was stirred at room temperature for 5 minutes, then sonicated in an 80 W ultrasonic oscillator for 5 minutes. Subsequently, 40 mg of azobisisobutyronitrile (AIBN) was added, and the mixture was stirred at room temperature for 5 minutes. The resulting precursor solution was then injected into a cuboid mold with a length of 110 mm, a width of 75 mm, and a thickness of 4 mm. After vacuuming for 1 minute to remove air bubbles, the mold was placed in a 60 °C oven for thermal polymerization for 12 hours, followed by thermal polymerization in an 80 °C oven for 2 hours. Finally, the mold was annealed in a 100 °C oven for 1 hour to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance. The doping amount of the mHRI-CPDs with surface-modified acryloyloxy polymerizable groups was 1.0 wt%.

[0045] By simply changing the doping amount of mHRI-CPDs, such as 0.5wt% or 1.5wt%, while maintaining the same preparation conditions as in this embodiment, carbonized polymer dot / polymer hybrid light guide plates with different light guiding properties and high visible light transmittance can be obtained. A schematic diagram of this type of carbonized polymer dot / polymer hybrid light guide plate is shown below. Figure 2 As shown, the carbonized polymer dots are uniformly dispersed in the polymer matrix. Due to the difference in refractive index between the two, the carbonized polymer dots act as light scattering units, thereby controlling the light scattering behavior. The performance parameters of this light guide plate are shown in Table 1, and the transmittance is as follows: Figure 7 As shown, the visible light transmittance of each group (1-0.5wt%, 1-1.0wt%, and 1-1.5wt%) exceeded 90%.

[0046] Example 2

[0047] 875 μL of 2-aminobenzylthiophenol and 2102 mg of 2,2'-dithiobenzoic acid were dissolved in 40 mL of a mixture of acetic acid and deionized water (5:5 volume ratio). The mixture was ultrasonically vibrated until homogeneous and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 180 °C for 8 hours. After the reaction, the solution in the reactor was centrifuged at 10,000 rpm for 5 minutes to remove the supernatant. The bottom precipitate was washed three times with dichloromethane, and the resulting powder was dried in a 40 °C oven to obtain 1018 mg of HRI-CPDs. The refractive index of the HRI-CPDs at 473 nm was 1.7225. The average particle size of the HRI-CPDs was 4.5 nm. Transmission electron microscopy (TEM) images are shown below. Figure 3 As shown, HRI-CPDs have clear morphology and uniform particle size.

[0048] The obtained 1018 mg HRI-CPDs and an equal mass of triethylamine were added to anhydrous tetrahydrofuran. The mixture was placed in an ice-salt bath and the temperature was lowered to -6°C. After stirring for 15 minutes, a mixed solution was obtained. 1018 mg acryloyl chloride was added dropwise to the mixed solution while stirring. The reaction was stopped after stirring for 1 hour. The reaction mixture was filtered to remove insoluble solids. The filtrate was distilled under reduced pressure to remove organic solvents, yielding 927 mg of mHRI-CPDs with surface-modified acryloyloxy polymerizable groups.

[0049] 400 mg of mHRI-CPDs with surface-modified acryloyloxy polymerizable groups were dissolved in 40 g of methyl acrylate. The mixture was stirred at room temperature for 5 minutes, then sonicated in an 80 W ultrasonic oscillator for 5 minutes. Subsequently, 40 mg of 1-hydroxy-cyclohexyl-phenyl ketone and 10 mg of azobisisobutyronitrile were added. After stirring at room temperature for 5 minutes, the precursor solution was injected into a cuboid mold with a length of 110 mm, a width of 75 mm, and a thickness of 2 mm. After vacuuming for 1 minute to remove air bubbles, the mold was placed in a 50 W UV curing lamp for 1 hour for curing. Then, it was placed in an 80 °C oven for thermal polymerization for 2 hours, and finally annealed in a 100 °C oven for 1 hour to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance. The doping amount of the mHRI-CPDs with surface-modified acryloyloxy polymerizable groups was 1.0 wt%. This light guide plate exhibits excellent visible light transmittance and outstanding light guiding performance. The high visible light transmittance can be attributed to the uniform distribution of carbonized polymer nanoparticles within the polymer matrix. Related transmission electron microscopy characterization is as follows: Figure 4 As shown in the figure, electron microscopy of the ultrathin sections reveals that the morphology and structure of mHRI-CPDs are maintained after copolymerization with polymer monomers, with no obvious aggregation behavior, which is key to the high visible light transmittance. The performance parameters of this light guide plate are shown in Table 1, and the transmittance is as follows: Figure 7 As shown, the visible light transmittance is greater than 90%.

[0050] Example 3

[0051] 875 μL of m-aminothiophenol and 1240 mg of thiosalicylic acid were dissolved in 40 mL of a mixture of propionic acid and deionized water (volume ratio of propionic acid to deionized water 7:3). The mixture was ultrasonically vibrated to ensure homogeneity and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 180 °C for 8 hours. After the reaction, the solution in the reactor was centrifuged at 10,000 rpm for 5 minutes to remove the supernatant. The bottom precipitate was washed three times with dichloromethane, and the resulting powder was dried in an oven at 40 °C to obtain 1241 mg of HRI-CPDs. The average particle size of the HRI-CPDs was 7.3 nm, and the refractive index at 473 nm was 1.7159.

[0052] The obtained 1241 mg of HRI-CPDs and an equal mass of triethylamine were added to anhydrous 1,4-dioxane. The mixture was placed in an ice-salt bath and the temperature was lowered to -5°C. After stirring for 20 minutes, a mixed solution was obtained. 1241 mg of cinnamoyl chloride was added dropwise to the mixed solution while stirring. The reaction was stopped after stirring for 3 hours. The reaction mixture was filtered to remove insoluble solids. The filtrate was then subjected to vacuum distillation to remove the organic solvent, yielding 1102 mg of mHRI-CPDs with a surface modified with 3-phenylacryloyloxy polymerizable groups. Cinnamoyl chloride was chosen as the surface modifier in this step because it modifies the surface of HRI-CPDs with 3-phenylacryloyloxy polymerizable groups, thereby increasing the solubility of mHRI-CPDs in styrene.

[0053] 1000 mg of mHRI-CPDs with surface-modified 3-phenylacryloyloxy polymerizable groups were dissolved in 40 g of styrene. The mixture was stirred at room temperature for 5 minutes, then sonicated in an 80 W ultrasonic oscillator for 5 minutes. Subsequently, 40 mg of azobisisobutyronitrile (AIBN) was added, and the mixture was stirred at room temperature for 5 minutes. The resulting precursor solution was then injected into a cuboid mold with a length of 90 mm, a width of 60 mm, and a thickness of 4 mm. After vacuuming for 1 minute to remove air bubbles, the mold was placed in a 60 °C oven for thermal polymerization for 12 hours, followed by thermal polymerization in an 80 °C oven for 2 hours. Finally, it was annealed in a 100 °C oven for 1 hour to obtain a high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate. The doping amount of mHRI-CPDs with surface-modified 3-phenylacryloyloxy polymerizable groups was 2.5 wt%. Since the basic light transmittance of polystyrene is lower than that of polymethyl methacrylate (PMMA), the light transmittance of the resulting light guide plate is lower than that of Example 1. The actual light guide plate and its light guiding effect are shown in the following figures. Figure 5 As shown, Figure 5 (a) is a schematic diagram of the high visible light transmittance of the carbonized polymer dot / polymer hybrid light guide plate prepared in Example 3. The visible light transmittance is very high and there is almost no color. Figure 5 (b) is a view of the high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate prepared in Example 3 before light guiding and illumination. It can be seen that the prepared light guide plate has a smooth surface and a large size. Figure 5 (c) is a schematic diagram of the light guiding effect of the high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate prepared in Example 3, showing uniform light emission from the surface. The performance parameters of this light guide plate are shown in Table 1, and the transmittance is as follows: Figure 7 As shown, the visible light transmittance is greater than 85%.

[0054] Example 4

[0055] 931 mg of o-aminophenol and 1137 mg of salicylic acid were dissolved in 40 mL of a mixture of formic acid and deionized water (volume ratio of formic acid to deionized water 9:1). The mixture was ultrasonically vibrated until homogeneous and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 180 °C for 8 hours. After the reaction, the solution in the reactor was centrifuged at 10,000 rpm for 5 minutes to remove the supernatant. The bottom precipitate was washed three times with dichloromethane, and the resulting powder was dried in a 40 °C oven to obtain 1235 mg of HRI-CPDs. Since o-aminophenol and salicylic acid do not contain sulfur, the refractive index of the carbonized polymer is reduced. The average particle size of the HRI-CPDs is 3.4 nm, and the refractive index at 473 nm is 1.6935.

[0056] The obtained HRI-CPDs and an equal mass of sodium acetate were added to anhydrous tetrahydrofuran. The mixture was placed in an ice-water bath and the temperature was lowered to 0°C. After stirring for 10 minutes, a mixed solution was obtained. 1235 mg of 2-butenoyl chloride was added dropwise to the mixed solution while stirring. The reaction was stopped after stirring for 1 hour. The reaction mixture was filtered to remove insoluble solids. The organic solvent in the filtrate was removed by vacuum distillation to obtain 1068 mg of mHRI-CPDs with 2-butenoyloxy polymerizable groups on the surface.

[0057] 800 mg of mHRI-CPDs with surface-modified 2-butenoyloxy polymerizable groups were dissolved in 40 g of butyl methacrylate. The mixture was stirred at room temperature for 5 minutes, then sonicated in an 80 W ultrasonic oscillator for 5 minutes. Subsequently, 50 mg of 2-hydroxy-2-methyl-1-phenyl ketone and 15 mg of benzoyl peroxide were added. After stirring at room temperature for 5 minutes, the precursor solution was injected into a cuboid mold with a length of 90 mm, a width of 60 mm, and a thickness of 3 mm. After vacuuming for 1 minute to remove air bubbles, the mold was cured under a 50 W UV lamp for 1 hour. It was then thermally polymerized in an 80 °C oven for 2 hours, and finally annealed in a 100 °C oven for 1 hour to obtain a high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate. The doping amount of the mHRI-CPDs with surface-modified 2-butenoyloxy polymerizable groups was 2.0 wt%. The display effect of this light guide plate in an LCD display is shown in the image below. Figure 6 As shown in Figure 1, (a) shows the display effect of the LCD screen before the backlight of the light guide plate is turned on; (b) shows the display effect of the LCD screen after the backlight of the light guide plate is turned on. It can be seen that the screen brightness is uniform and high, meeting the requirements of practical applications. The performance parameters of the light guide plate are shown in Table 1, and the transmittance is as follows: Figure 7 As shown, the visible light transmittance is greater than 85%.

[0058] Example 5

[0059] 937 μL of p-aminothiophenol and 1359 mg of salicylic acid were dissolved in 40 mL of a mixture of propionic acid and deionized water (volume ratio of propionic acid to deionized water 8:2). The mixture was ultrasonically vibrated to ensure homogeneity and then transferred to a 100 mL hydrothermal reactor. The reaction was carried out at 200 °C for 6 hours. After the reaction, the solution in the reactor was centrifuged at 10,000 rpm for 5 minutes to remove the supernatant. The bottom precipitate was washed three times with dichloromethane. The resulting powder was dried in an oven at 30 °C to obtain 1632 mg of HRI-CPDs. The average particle size of the HRI-CPDs was 9.6 nm, and the refractive index at 473 nm was 1.7032.

[0060] The obtained HRI-CPDs and an equal mass of N-diisopropylethylamine were added to anhydrous acetonitrile. The mixture was placed in an ice-water bath to lower the temperature to 0°C. After stirring for 5 minutes, a mixed solution was obtained. 1632 mg of 3,3-dimethylacryloyl chloride was added dropwise to the mixed solution while stirring. After stirring for 5 hours, the reaction was stopped. The reaction mixture was filtered to remove insoluble solids. The filtrate was subjected to vacuum distillation to remove organic solvents, yielding 1439 mg of mHRI-CPDs with surface-modified 3,3-dimethylacryloyloxy polymerizable groups.

[0061] 1200 mg of mHRI-CPDs with surface-modified 3,3-dimethacryloyloxy polymerizable groups were dissolved in a mixed monomer consisting of 20 g butyl methacrylate and 20 g methyl methacrylate. The mixture was stirred at room temperature for 5 minutes, then sonicated in an 80 W ultrasonic oscillator for 5 minutes. Subsequently, 60 mg of azobisisobutyronitrile (AIBN) was added, and the mixture was stirred at room temperature for 5 minutes. The precursor solution was then injected into a cuboid mold with a length of 90 mm, a width of 60 mm, and a thickness of 2 mm. After vacuuming for 1 minute to remove air bubbles, the mold was placed in an 80 °C oven for thermal polymerization for 12 hours, followed by thermal polymerization in a 90 °C oven for 2 hours. Finally, it was annealed in a 100 °C oven for 1 hour to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance. The doping amount of the mHRI-CPDs with surface-modified 3,3-dimethacryloyloxy polymerizable groups was 3.0 wt%. The performance parameters of the light guide plate are shown in Table 1, and the transmittance is as follows: Figure 7 As shown, the visible light transmittance is greater than 85%.

[0062] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general methods used herein can be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance, comprising the following steps: a. Dissolve 0.1 to 5 parts by mass of mHRI-CPDs with polymerizable groups on the surface in 100 parts by mass of polymerizable active monomer to obtain mixed solution A; b. Stir the mixed solution A prepared in step a at room temperature for 3-8 minutes, and then sonicate it in a 60-100W ultrasonic oscillator for 3-8 minutes; then add 0.1-0.5 parts by weight of initiator 1 to the mixed solution, stir at room temperature for 3-8 minutes to prepare a precursor solution; inject the precursor solution into a cuboid mold, evacuate for 1-3 minutes to remove air bubbles, first thermally polymerize at 50-70℃ for 10-15 hours, then thermally polymerize at 75-85℃ for 1-3 hours, and finally anneal at 100-110℃ for 1-2 hours to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance; Alternatively, stir the mixed solution A prepared in step a at room temperature for 3-8 minutes, and then sonicate it in a 60-100W ultrasonic oscillator for 3-8 minutes; then add 0.1-0.5 parts by weight of initiator 2 to the mixed solution, stir at room temperature for 3-8 minutes to prepare a precursor solution; inject the precursor solution into a cuboid mold, vacuum for 1-3 minutes to remove air bubbles, first place it in front of a 40-60W UV curing lamp for 1-3 hours, then thermally polymerize it at 75-85℃ for 1-3 hours, and finally anneal it at 100-110℃ for 1-2 hours to obtain a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance; The polymerizable active monomer mentioned in step a is one or a mixture of several of allyl diethylene glycol carbonate, styrene, methyl acrylate, methyl methacrylate, butyl methacrylate, and N,N-dimethylacrylamide. The preparation method of the mHRI-CPDs with polymerizable groups modified on the surface described in step a is as follows: (1) Preparation of HRI-CPDs by hydrothermal method Weigh 2-aminobenzylthiophenol and thiosalicylic acid in a molar ratio of 1:0.8~1.2 and dissolve them in an acidic aqueous solution. After ultrasonic vibration to ensure uniform mixing, transfer the mixture to a hydrothermal reactor and react at 140~220℃ for 2~8 hours. After the reaction, remove the supernatant by centrifugation. Wash the bottom precipitate 3~5 times with dichloromethane and then dry it at 20~40℃ to obtain HRI-CPDs. (2) Preparation of mHRI-CPDs The HRI-CPDs prepared in step (1) and an equal mass of acid-binding agent were added to anhydrous organic solvent, and the mixture was placed in an ice-salt bath to lower the temperature to -10~0℃. The mixture was stirred for 10~20 minutes to obtain a mixed solution. Under stirring, an equal mass of surface modifier was added to the mixed solution and the reaction was carried out for 1~10 hours. After the reaction was completed, the reaction mixture was filtered and the organic solvent was removed from the filtrate by vacuum distillation to obtain mHRI-CPDs with polymerizable groups on the surface. The surface modifier is one or more of acryloyl chloride, methacryloyl chloride, 2-butenoyl chloride, 3,3-dimethylacryloyl chloride, cinnamoyl chloride, and p-fluorocinnamoyl chloride.

2. The method for preparing a high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate as described in claim 1, characterized in that: The initiator 1 mentioned in step b is one or a mixture of several of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, dicumyl peroxide, and tert-butyl peroxide.

3. The method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance as described in claim 1, characterized in that: The initiator 2 mentioned in step b is one or a mixture of several of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, and benzophenone, or is one or more of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, and benzophenone mixed with azobisisobutyronitrile, azobisisoheptanenitrile, or dimethyl azobisisobutyrate. A mixture of one or more of benzoyl peroxide, dicumyl peroxide, and tert-butyl peroxide; and one or more of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, and benzophenone, in a mass ratio of 3 to 5:1 with one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, dicumyl peroxide, and tert-butyl peroxide.

4. The method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance as described in claim 1, characterized in that: The thickness of the prepared high visible light transmittance carbonized polymer dot / polymer hybrid light guide plate is 0.1~20 mm.

5. The method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance as described in claim 1, characterized in that: The particle size of the HRI-CPDs and mHRI-CPDs is between 2 and 10 nanometers.

6. The method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance as described in claim 1, characterized in that: In step (1), thiosalicylic acid is replaced by one or more of 2,2'-dithiodibenzoic acid and salicylic acid, and 2-aminobenzylthiophenol is replaced by one or more of p-aminobenzylthiophenol, m-aminobenzylthiophenol, m-aminophenol, p-aminophenol, and o-aminophenol.

7. The method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance as described in claim 1, characterized in that: In step (1), the acidic aqueous solution contains one or more of formic acid, acetic acid, and propionic acid. The total volume of acid and water is 100%, of which the volume of acid is 20% to 90%.

8. The method for preparing a carbonized polymer dot / polymer hybrid light guide plate with high visible light transmittance as described in claim 1, characterized in that: In step (2), the acid-binding agent is one or more of N-diisopropylethylamine, triethylamine, pyridine, sodium acetate, sodium carbonate, and potassium carbonate, and the anhydrous organic solvent is one or more of anhydrous acetone, anhydrous acetonitrile, anhydrous tetrahydrofuran, anhydrous 1,4-dioxane, and anhydrous propylene glycol methyl ether acetate.